Itinerary and Mobile Code Patterns for Emerging Mobile Agent Systems in Large Scale Distributed Environments - Chowhan, R.S; Dayya, P (International Journal of Computer Sciences and Engineering, 2025)
Patters in mobile agents help to design different applications which have non-permanent connections by adding the mobility code, improved networks, goal sustainability and machine based intelligence. Also the agent patterns mainly provide easy methods of developing the agent-based applications which are used or operated in open and large-scale distributed environments. It can provide various facilities like mobility, working in intermittent connections, autonomous execution, and many more that can allow sustainability of mobile agent based systems amidst of existing technologies like client-server. This paper gives an overview of the patterns of the mobile agents in mobile computing. Also the discussion covers the patterns and their usage, architectures, languages, applications, and the implementation challenges that are likely to be faced. This paper mainly discusses mobile agent which is a new technology that can be used in designing, implementing, and maintaining distributed systems. The discussion covers the patterns for mobile agents in the mobile computing applications.